History and Cultural Memory in Neo-Victorian Fiction Victorian Afterimages - Mitchell, Kate.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2010)
A PDF version of this book is available for free in open access via the OAPEN Library platform, www.oapen.org. Arguing that neo-Victorian fiction enacts and celebrates cultural memory, this book uses memory discourse to position these novels as dynamic participants in the contemporary historical imaginary.
Keywords: European literature; Literature -- Philosophy; Culture -- Study and teaching; Literature, Modern -- 20th century; Fiction; European Literature; Literary Theory; Cultural Theory; Twentieth-Century Literature; Fiction Literature